Philanthropy and the National Park Service - Vaughn, Jacqueline; Cortner, Hanna J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
As the National Park Service prepares for its 2016 centennial, this book provides an in-depth analysis of the role of philanthropy and the national parks - exploring the challenges faced when working with non-profit philanthropic partners.
Keywords: Science; Science; Science, general